Online English Language Teaching in the Midst of Covid-19 Pandemic: Non EFL Students' Feedback and Response - Sukmawati Sukmawati; Sujarwo Sujarwo; Dewi Nidia Soepriadi; Nurul Amaliah (AT-TA'LIM, 2022)
The Covid-19 pandemic has changed the order of learning that has been carried out by lecturers at universities. Learning shifted from traditional to online. Online learning is one of the main strategies that must be carried out by lecturers in order to ensure that the learning process continues. The study aims to determine students’ responses and feedbacks during online learning in English courses during Covid - 19. The research method used descriptive quantitative method. Data were taken using questionnaires and interviews. The questionnaire was prepared through Google Form and a link was sent to students, and lecturers via WhatsApp. The population and sample in this study were students of the DIII TLM study program, S1 Pharmacy, S1 PGSD and S1 ARS at Universitas Megarezky who took English courses. The instrument used is a response questionnaire and student feedback during online learning. Based on data processing and analysis that online learning carried out by lecturers in English courses has been effective, efficient, varied, helping students understand the material, forming independent learning, and increasing student active participation in learning. There are several important findings regarding online learning during the COVID-19 pandemic. Zoom, WhatsApp and Google Classroom are the most widely used applications as learning media. There are several obstacles experienced by teachers and students during the implementation of online learning related to internet access and quotas. Both students and teachers long for face-to-face learning activities directly in the classroom. Both students and teachers long for face-to-face learning activities directly in the classroom. Zoom, WhatsApp and Google Classroom are the most widely used as learning media. There are several obstacles experienced by teachers and students during the implementation of online learning related to internet access and quotas. Both students and teachers long for face-to-face learning activities directly in the classroom.